Changes of thermal properties and microstructure of nano‐ZnO/polylactic acid composite films during Zn migration. Issue 1 (1st September 2020) - Lu, Wangwei; Jiang, Kai; Chu, Zhuangzhuang; Yuan, Minglong; Tang, Zhenya; Qin, Yu‐Yue
Abstract : In this study, polylactic acid (PLA) films with different nano‐ZnO concentration (0, 1, 3, 5, 7, 9, and 15%wt) were obtained by casting method. Overall migration values and specific migration values were studied in different food simulants (10% [ v /v] ethanol and isooctane). The results demonstrated that overall migration of the composite films and specific migration of Zn 2+ was higher in 10% ( v /v) ethanol solution than in isooctane solution. The release of Zn 2+ was affected by the percentage of nano‐ZnO in the composite films and food simulants. The migration of Zn in this study was mainly caused by polymer softening and degradation leading to the dissolution of Zn. Scanning electron microscope analysis indicated that with the migration of Zn 2+, the structure of the composite films changed greatly. Differential scanning calorimeter analysis indicated that the thermal stability was decreased and the glass transition temperature and crystallization temperature were reduced. Abstract : SEM images of PLA‐1 (a), PLA‐3 (b), PLA‐5 (c), PLA‐7 (d), PLA‐9 (e), and PLA‐15 (f) on days 1, 3, 5, 10, and 20, respectively.